ANALISA KEPADATAN DAN IDENTIFIKASI AKTIVITAS PEMANFAATAN SUMBERDAYA MOLUSKA DI PERAIRAN PANTAI TANJUNG TIRAM, DESA POKA - Hulopi, Mahriyana; Mose, Sendy W; Uneputty, Prulley A (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2021)
Increasing the activity of the utilization of mollusc resources by the community, both domiciled around and outside the waters of Tanjung Tiram Beach can have an impact on the sustainability of these resources. This study aims to analyze the density of mollusc and identify the activity of utilization of mollusc resources in the waters of Tanjung Tiram Beach. The study was conducted in October-November 2019 in the waters of Tanjung Tiram Beach, Poka Village. Data collection is taken using the quadratic linear transect method and interviews. The results showed the highest density was represented by Nassarius quadrasi for the gastropod class while for the bivalvia class it was represented by Marcia sp. The high density in both types of mollusc is due to habitat suitability supported by the quality of the waters. Based on respondent data, there are 20 types of mollusc that are used both for consumption, sale and as raw materials for making accessories through the